Table of Content - - (Journal of Humanities & Social Sciences, 2024)
Table of Content: 1. The role of private associations in enhancing voluntary work in Jeddah Mr. Bayan Hamed Al-Harbi 2. Scientific Miraculous in Holy Quran – Terminology Issue – Mr. Mohamad Mostafa Charmand 3. The role of digital public relations in promoting domestic tourism Saudi Airlines Case Study for the year 2024 Mr. Abdulla Hmood Almutairi, Dr. Mohammed Abdulaziz Alheizan 4. The Contribution of Agricultural Activities to Rural Development in Upper Saiss and the Challenges to its Sustainability: A Case Study of the Matmata and Bouhlo Municipalities (Taza Province, Morocco) during the Period 2020-2024 Ms. Fatima Ghmimed, Mr. Mohamed El-Fazziki, Dr. Jaouad El-Bazoui, Dr. Abdelouahed Bouberria 5. Spatial variation of rainfall in the Medina region for the period (1985 – 2020) Ms. Najwa Mounir Al-Sahli, Dr. Fayidah Kamil Buqiri 6. Social Support’s Impact on Psychological Distress and Life Satisfaction among Saudi Women in Makkah City Dr. Najwa Helal Alharbi